Pilot study on virtual imaging for patient information on radiotherapy planning and delivery. Issue 3 (August 2015) - Sulé-Suso, J.; Finney, S.; Bisson, J.; Hammersley, S.; Jassel, S.; Knight, R.; Hicks, C.; Sargeant, S.; Lam, K.-P.; Belcher, J.; Collins, D.; Bhana, R.; et al.
Abstract It is widely accepted that health professionals might sometimes underestimate cancer patients' needs for information on the complex process of radiotherapy (RT) planning and delivery. Furthermore, relatives might also feel excluded from the treatment of their loved ones. This pilot study was carried out in order to assess whether both patients and their relatives would welcome further information on RT planning and delivery using the virtual reality (VR) system VERT. One hundred and fifty patients with different types of cancer receiving radical RT were included in the study. Patients and relatives were shown using VERT on a one-to-one basis with an oncologist or a radiographer, a standard room where RT is given, a linear accelerator, and how RT is planned and delivered using their own planning CT Scans. Patients welcomed this information as it helped them to reduce their fears about RT. Relatives felt also more involved in the treatment of their loved one. The results obtained in this pilot study show that VR aids could become an important tool for delivering information on RT to both patients and relatives.